2022
DOI: 10.1177/0143831x221086017
|View full text |Cite
|
Sign up to set email alerts
|

Self-employment experience effects on well-being: A longitudinal study

Abstract: The notion that self-employed individuals are more satisfied with their jobs than wage-employees has found broad empirical support. Previous research exploring the well-being effects of self-employment typically relies on direct cross-sectional comparisons between wage-employees and self-employed or on longitudinal investigations of transitions in or out of self-employment. In this study, the authors use individuals’ employment status histories in British longitudinal data to examine how accumulated self-emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 123 publications
(210 reference statements)
1
1
0
Order By: Relevance
“…The analysis of the relevance of gender and job type (permanent, contracted, or selfemployed) on job satisfaction showed that only job type was relevant for job satisfaction. Self-employed workers were more satisfied than contracted employees, a result that is consistent with previous findings [58,59]. In addition, marital status was not related to job satisfaction, as found in previous research [11].…”
Section: Discussionsupporting
confidence: 91%
“…The analysis of the relevance of gender and job type (permanent, contracted, or selfemployed) on job satisfaction showed that only job type was relevant for job satisfaction. Self-employed workers were more satisfied than contracted employees, a result that is consistent with previous findings [58,59]. In addition, marital status was not related to job satisfaction, as found in previous research [11].…”
Section: Discussionsupporting
confidence: 91%
“…The relationship between self-employment and well-being has also been explored, with studies indicating that establishing this relationship is challenging due to simultaneous selection and contextual effects (Xiu & Ren, 2022). Moreover, the experience of self-employment has been found to impact facets of well-being, including satisfaction with job, leisure, and income (Litsardopoulos et al, 2022). Additionally, the relationship between precarious employment and subjective well-being in Korean wage workers has been investigated, revealing a negative impact on subjective well-being (Choi et al, 2020).…”
Section: Socio-economic Implicationsmentioning
confidence: 99%
“…The relationship between self-employment and wellbeing has also been explored, with studies indicating that establishing this relationship is challenging due to simultaneous selection and contextual effects (Xiu & Ren, 2022). Moreover, the experience of self-employment has been found to impact facets of well-being, including satisfaction with job, leisure, and income (Litsardopoulos et al, 2022). Additionally, the relationship between precarious employment and subjective well-being in Korean wage workers has been investigated, revealing a negative impact on subjective well-being (Choi et al, 2020).…”
Section: Socio-economic Implicationsmentioning
confidence: 99%